Analysis, Development, And Simulation Of A Mission System For MUM-T Operational Scenarios - Cicalini, M.; Lukasiewicz, M.S.; Frisini, D.; Masarati, P. (My University, 2024)
This paper describes the modelling and the simulation of a mission system for manned-unmanned teaming operational scenarios, with a specific focus on rotorcraft applications. To accomplish the task, a high-level architecture to enable teaming is defined and prototypes of a Pilot Onboard Station and a Ground Control Station have been realized. Both prototypes are coded with open-source software like QGroundControl, and are meant to cover all the flight phases of planning, monitoring, and decision support. They were integrated in a helicopter flight simulator specifically designed for teaming simulation, in which the aeromechanical and feedback implementation of the main vehicle are based on an MBDyn/Simulink architecture and the uncrewed vehicles are simulated using AirSim with PX4-Autopilot as flight controller. The involved graphics engine is Unreal Engine 5, chosen due to its high graphical realism. With this configuration, a final test campaign was performed, from hardware and software setup to the description of results. These are encouraging in terms of required workload and intuitiveness, opening the way to more mature implementations.